Propylthiouracil-induced ANCA-associated vasculitis complicated by granulocytopenia and hemophagocytosis: a case report - Zhou, Huilin; Lai, Shuchang; Chen, Jinyi; Wang, Yi; Fu, Shasha; Chen, Zongcun (Frontiers in Medicine, 2025)
ObjectiveTo analyze a rare case of ANCA-associated vasculitis (AAV) complicated by hemophagocytosis and granulocytopenia induced by long-term propylthiouracil (PTU) therapy, providing insights for clinical diagnosis and management.MethodsA retrospective analysis was conducted on the clinical data and treatment course of a patient who developed AAV with hemophagocytosis and granulocytopenia after prolonged PTU use.ResultsUpon admission, granulocytopenia secondary to PTU was suspected. Despite transient recovery of leukocyte counts with anti-infective therapy and granulocyte colony-stimulating factor (G-CSF), recurrent leukopenia and intermittent fever persisted. Bone marrow aspiration revealed hemophagocytic cells, while serologic testing showed positivity for both PR3-ANCA and MPO-ANCA. A definitive diagnosis of PTU-induced AAV was established. Glucocorticoid therapy normalized body temperature and restored leukocyte levels. Follow-up demonstrated resolution of thyrotoxicosis, stabilized leukocyte counts, and afebrile status.ConclusionLong-term PTU therapy may trigger AAV accompanied by hemophagocytosis. Clinicians should consider screening for hemophagocytic lymphohistiocytosis (HLH) in such cases to guide timely immunosuppressive intervention.